Evaluating the Economic Impact of Water Regulation and Sustainability on Urban Supply Chain Facility Planning - Felicia Jefferson; Jairo De Jesus; Erick Jones; Deborah J. Ortiz (International Journal of Supply Chain Management, 2014)
Abstract Supply chain facilities, specifically manufacturing plants that are located near urban areas, are often regulated by distinct local municipalities, state ordinances and federal regulations. This transcript highlights one of the more heavily regulated type of facilities - a meat food processing plant that requires a special permit for its industrial use of sewer services as it meets one or more criteria of select discharge regulations. This type of facility is heavily regulated by a local municipality to avoid water shortages and is using penalties and taxes to encourage conservation and raise revenue. For scenario description purposes, we highlight sample data from a plant facility in the east coast in the lower southeastern part of the United States. We incorporate the tax and penalty scenario from a municipality in the state of Georgia. This research describes the steps and processes used by the plant facility to make certain that it complies with the rules and regulations of the sewer service permit, along with ensuring compliance with environmental regulations and policies, while providing evidence of the economic benefits for plant facilities to incorporate sustainable practices in the overall wastewater treatment process. Keywords supply chain facility, water regulation, wastewater treatment, sustainability, predictive modelling, cost benefit savings